2022
DOI: 10.3390/healthcare10122575
|View full text |Cite
|
Sign up to set email alerts
|

Body Mass Index and Clinical Outcomes in Adult COVID-19 Patients of Diverse Ethnicities

Abstract: (1) Background: Body mass index (BMI) was observed to affect COVID-19 outcomes; however, the complete spectrum of clinical outcomes concerning BMI remains unexplored. The current study aimed to investigate the correlation between BMI and the severity and mortality of COVID-19, as well as ICU admission, radiological findings, clinical presentation, and time to viral clearance. (2) Methods: This retrospective study included 1796 multiethnic patients with COVID-19 treated at NMC Royal Hospital, Abu Dhabi, UAE. (3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 40 publications
0
4
0
Order By: Relevance
“…This observation was recently confirmed in a meta-analysis of 34,390 patients from 12 different studies identifying the association of obesity with poor outcome, mortality, and severity in COVID-19 patients [12]. Likewise, several other studies identified obesity as a risk factor for worse disease outcomes of COVID-19, suggesting that higher BMI may be useful for risk stratification [13][14][15].…”
Section: Introductionmentioning
confidence: 68%
See 1 more Smart Citation
“…This observation was recently confirmed in a meta-analysis of 34,390 patients from 12 different studies identifying the association of obesity with poor outcome, mortality, and severity in COVID-19 patients [12]. Likewise, several other studies identified obesity as a risk factor for worse disease outcomes of COVID-19, suggesting that higher BMI may be useful for risk stratification [13][14][15].…”
Section: Introductionmentioning
confidence: 68%
“…Obesity increases the susceptibility and risk for SARS-CoV-2 infections, a worse COVID-19 disease trajectory and COVID-19-related death [13]. Circulating levels of chemerin, leptin, and galectin-3 are commonly elevated, while serum adiponectin levels are reduced in the obese and all of those changes are related to metabolic diseases (Figure 2) [5,28,43].…”
Section: Discussionmentioning
confidence: 99%
“…These results were in line with the study by Palaiodimos et al [ 11 ], which found that obesity leads to a four-fold increase in in-hospital mortality. Similarly, when comparing obese patients to a normal BMI range (20–29.9), a study conducted in the United Arab Emirates including 1796 by Hafez et al [ 12 ] showed a non-significant increase in mortality for patients with Class III obesity (BMI ≥ 40). Another study conducted in Japan by Lee et al [ 13 ], which included 1837 patients, did not show significant differences in morality among the BMI classes when compared to each other.…”
Section: Discussionmentioning
confidence: 99%
“…5,6 Obesity, as a known risk factor for respiratory infections, was reported to be associated with unpleasant clinical outcomes in patients with COVID-19. 7,8 A systematic review of the studies on obesity and mortality of COVID-19 patients in the Asian and western countries reported that the mortality of COVID-19-hospitalized patients is related to obesity. 9 The exact mechanism of the effect of obesity on patients with COVID- 19 is not yet clear.…”
Section: Introductionmentioning
confidence: 99%